Home and day‐care microenvironment exposure to Blomia tropicalis allergens and their associations with salivary eosinophilic cationic protein (ECP) among preschool children in Singapore. (17th July 2019) - Sultan, Zuraimi; Koh, Gerald Choon‐Huat; Chew, Fook Tim; Ng, Vivian; Koh, David Soo Quee; Tham, Kwok Wai
Abstract: To date, exposure studies linking dust‐mite allergens with asthma and allergic morbidities have typically relied on sampling from representative locations in the home for exposure assessment. We determine the effects of differing microenvironments allergen exposures on asthma and asthma severity among 25 case and 31 control preschool children in Singapore. Blo t 5 allergen levels in various niches from the children's home and day‐care microenvironments as well as their Blo t 5 time‐weighted concentrations were determined. Eosinophilic cationic protein (ECP) levels from the children's saliva as markers for airway inflammation were obtained. Salivary ECP levels were higher in children with asthma than those without and the strength of association increased with higher salivary ECP levels. Although there was no relationship between time‐weighted Blo t 5 concentrations with salivary ECP levels among the controls, a positive statistically significant relationship was noted among cases, demonstrating the effects of cumulative exposure on asthma severity. Avoidance measures to reduce Blo t 5 allergen exposure should include all microenvironments that asthmatic children are exposed throughout the day.